Establishing reference ranges for ambulatory electrocardiography parameters: meta-analysis. Issue 22 (20th July 2020) - Williams, Curtis B; Andrade, Jason G; Hawkins, Nathaniel M; Cheung, Christopher; Krahn, Andrew; Laksman, Zachary W; Bennett, Matthew T; Heilbron, Brett; Chakrabarti, Shanta; Yeung-Lai-Wah, John A; Deyell, Marc W
Abstract : Objective: Despite the widespread and increasing use of ambulatory electrocardiography (ECG), there is no consensus on reference ranges for ambulatory electrocardiogram parameters to guide interpretation. We sought to determine population distribution-based reference ranges for parameters measured during ambulatory electrocardiogram in healthy adults, based on existing literature. Methods: We searched multiple databases from 1950 to 2020. Articles reporting original data from ≥24-hour ambulatory electrocardiogram monitoring in healthy adults were included. Data extraction and synthesis were performed according to Meta-analysis of Observational Studies in Epidemiology guidelines. The prevalence/mean and SD for common parameters (sinus pauses, conduction abnormalities and ectopy) were extracted by age group (18–39, 40–59, 60–79 and 80+ years). Results: We identified 33 studies involving 6466 patients. Sinus pauses of >3 s were rare (pooled prevalence <1%) across all ages. Supraventricular ectopy of >1000/24 hours increased with age, from 0% (95% CI 0% to 0%) in those aged 18–39 years to 6% (95% CI 0% to 17%) in those aged 60–79 years. Episodes of supraventricular tachycardia increased from 3% (95% CI 1% to 6%) in those aged 18–39 years to 28% (95% CI 9% to 52%) in those aged 60–79 years. Ventricular ectopy of >1000/24 hours also increased with age, from 1% (95% CI 0% to 2%) in those aged 18–39 years to 5% (95% CI 1% to 10%) in those aged 60–79 years. Episodes of non-sustained ventricular tachycardia ranged from 0% (95% CI 0% to 1%) in those aged 18–39 years to 2% (95% CI 0% to 5%) in those aged 60–79 years. Conclusion: Despite the limitations of existing published data, this meta-analysis provides evidence-based reference ranges for ambulatory electrocardiogram parameters and highlights significant age-dependent differences that should be taken into account during interpretation.